Report

9.4 – Solving Quadratic Equations By Completing The Square Ex. 1 a. Solve x2 – 12x + 36 = 0. Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x )(x )=0 Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0 Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0 (x – 6)2 = 0 Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0 √(x – 6)2 = √0 Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0 √(x – 6)2 = √0 x–6=0 Ex. 1 a. Solve x2 – 12x + 36 = 0. x2 – 12x + 36 = 0 (x – 6)(x – 6) = 0 √(x – 6)2 = √0 x–6=0 x=6 b. Solve x2 + 8x + 16 = 0. b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 √(x + 4)2 = √ 0 x+4=0 x = -4 b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 Want x2 + 10x + 25 b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 +4 +4 x2 + 10x + 25 = 4 b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 +4 +4 x2 + 10x + 25 = 4 (x + 5)2 = 4 b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 +4 +4 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2 b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 +4 +4 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2 x+5=2 b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 +4 +4 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2 x+5=2 x + 5 = -2 b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 +4 +4 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2 x+5=2 x + 5 = -2 x = -3 b. Solve x2 + 8x + 16 = 0. x2 + 8x + 16 = 0 (x + 4)(x + 4) = 0 (x + 4)2 = 0 x+4=0 x = -4 Ex. 2 a. Solve x2 + 10x + 21 = 0 by completing the square. x2 + 10x + 21 = 0 +4 +4 x2 + 10x + 25 = 4 (x + 5)2 = 4 x + 5 = ±2 x+5=2 x + 5 = -2 x = -3 x = -7 b. Solve x2 + 14x = 12 by completing the square. b. Solve x2 + 14x = 12 by completing the square. x2 + 14x = 12 Want x2 + 14x + 49 x2 + 14x + 49 = 61 (x + 7)2 = 61 x + 7 = ±√61 x = -7 ± √61 x ≈ 0.8 or x ≈ -14.8